Analisis Framing Pada Cover Majalah Tempo Edisi 16-22 September 2019 di Detik.Com dan Suara.Com - Noval Setiawan (Hikmah, 2020)
The news in the online media is no different than the media in general, namely the interests and ideological strengths of every existing media. With this research effort, we will see how framing is done by online media in seeing an event that will be reported. As well as see how the influence of ownership and online media efforts to maintain a neutral position and objectivity in the news. This study analyzes the coverage of the Jokowi pinocchio silhouette on the cover of the tempo magazine September 16-22, 2019 on Detik.com and Suara.com with a qualitative approach and uses the framing analysis method of the Zhong Pan and Geral M. Kosichi models.In the research process shows that the framing of the two media are very different. As Detik.com framing the news of the Jokowi pinocchio silhouette on the cover of the September 16-22 edition of the magazine maturity seems less objective and tends to use the expression of the magazine's Editor's Response, Setri Yasra, so the tempo magazine denies Jokowi's contempt. In contrast to Suara.com in its framing, it tends to seek objectivity in reporting in order to produce information that is in accordance with social reality, because it uses the expression of responses from politicians namely Ferdinand and Volunteer Jokowi who have no binding with tempo magazines.So Suara.com in reporting the tempo magazine cover was considered insulting Jokowi then reported to the press Council.Keywords: Pinocchio Silhouette, Tempo Magazine, Framing Analysis